Physiological responses and time-motion characteristics of 4-a-side small-sided game in young soccer players: The influence of different team formation methods - Köklü, Y.; Ersöz, G.; Alemdaroglu, U.; Asc, A.; Öskan, A. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the influence of different team formation methods on the physiological responses to and time-motion characteristics of 4-a-side small-sided games (SSG4) in young soccer players. Thirty-two young soccer players (age 16.2 ± 0.7 years; height 172.9 ± 6.1 cm; body mass 64.1 ± 7.7 kg) voluntarily participated in this study. Anthropometric measurements, technical tests, and maximum oxygen uptake (VO2max) tests were carried out on the players. The SSG4 teams were then created using 4 different methods: according to the coaches' subjective evaluation (CE), technical scores (TS), VO2max (AP), and VO2max multiplied by TSs (CG). The teams thus created played 4 bouts of SSG4 at 2-day intervals. During the SSG4, heart rate (HR) responses, distance covered, and time spent in HRmax zones were recorded. In addition, rating of perceived exertion (RPE) and blood lactate level (La-) were determined at the end of the last bout of each SSG4. Percent of HRmax (%HRmax), La-, and RPE responses during SSG4 were significantly higher for teams chosen according to AP and CG compared with that according to CE and TS (p < 0.05). In addition, teams chosen by AP and CG spent significantly more time in zone 4 (>90% HRmax ) and covered a greater distance in the high-intensity running zone (>18 km/h) than did teams formed according to TS. Moreover, AP teams covered significantly greater total distance than TS teams did (p < 0.05). In conclusion, to spend more time in both the high-intensity HR zone and the high-intensity running zone, the teams in SSG4 should be formed according to the players' VO2max values or the values calculated using both the VO2max and technique scores.